2021
DOI: 10.1021/acsami.1c12790
|View full text |Cite
|
Sign up to set email alerts
|

How to Choose an Interfacial Modifier for Organic Photovoltaics Using Simple Surface Energy Considerations

Abstract: Organic photovoltaics are typically composed of at least four different materials, including the donor and acceptor components of the bulk heterojunction, the interfacial layers at each electrode, the electrodes themselves, and solution additives that may persist in the final sandwich structure. The interplay of surface energies between these different layers is profoundly complex, as the deposition and annealing of one layer on top of another may be influenced by the surface energy of these interfaces. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The surface energies of PM6:Y6, PM6:Y6/PDINN-S, and PM6:Y6/PDINN were 19.0, 57.1, and 53.2 mN m –1 (Table S2) by the Owen formula . Solutions with high free energy materials are generally not conducive to wetting and diffusion of solids with a lower surface energy. , Thus, PDINN with relatively high surface energy impedes interlayer uniformity, while PDINN-S with suitable surface energy can form preferable compatibility with the upper/lower layers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The surface energies of PM6:Y6, PM6:Y6/PDINN-S, and PM6:Y6/PDINN were 19.0, 57.1, and 53.2 mN m –1 (Table S2) by the Owen formula . Solutions with high free energy materials are generally not conducive to wetting and diffusion of solids with a lower surface energy. , Thus, PDINN with relatively high surface energy impedes interlayer uniformity, while PDINN-S with suitable surface energy can form preferable compatibility with the upper/lower layers.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since PEDOT: PSS is a hydrophilic material, while the PTAA is a hydrophobic polymer, the surface tension of P–P HTL is highly dependent on the composition of each component. [ 42 ] This apparent transition in the contact angle of P–P HTL, varying from a value close to PEDOT: PSS to a value close to pristine PTAA, strongly implies that the coverage of PTAA on PEDOT: PSS increases with increasing concentration of its deposition solution. The corresponding surface energy is calculated according to the Owen method (Table S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure a, to characterize the morphology of the CP/Y6 blend film, BHJ-type films were prepared on PEDOT:PSS precast films using the same composition of CP/Y6 (1:1.5 wt ratio) with the OPV fabrication. It has been reported that the vertical distribution of each component in the blend film is related to the surface energy of the underlying layer . To characterize the distribution of CP/Y6 in the blend film formed on the PEDOT:PSS layer, we first determined the surface energies of CP and Y6 by measuring contact angles using water and glycerol.…”
Section: Resultsmentioning
confidence: 99%